Breastfeed4Ghana: Design and evaluation of an innovative social media campaign - Aryeetey, R.; Harding, K.; Carroll, G.; Lasisi, O.; Pérez‐Escamilla, R.; Young, M. (Maternal & Child Nutrition, 2019)
Although targeting health behaviour change through social media campaigns has gained traction in recent years, few studies have focused on breastfeeding social media campaigns. Within the context of rising social media utilization and recent declines in exclusive breastfeeding practices in Ghana, we implemented Breastfeed4Ghana, a Facebook‐ and Twitter‐based breastfeeding social media campaign. This study determined feasibility of implementing Breastfeed4Ghana and evaluated its impact on breastfeeding knowledge in Ghana. Key performance indicators of the campaign were monitored on social media platforms, Facebook and Twitter. An online cross‐sectional survey conducted across three time points (n = 451) assessed breastfeeding knowledge, campaign exposure, and understanding and acceptability of Breastfeed4Ghana among Ghanaian adults. Modified Poisson models were used to assess the relationship between campaign exposure and breastfeeding knowledge, adjusting for survey time point, sex, and parenthood status. The campaign acquired 4,832 followers. Based on follower demographics collected from Facebook and Twitter analytics, the target population was successfully reached. Campaign exposure among survey participants was 42.3% and 48.7% at midline and endline, respectively. Campaign acceptability was high (>90%), and >44% of those exposed to the campaign also shared the campaign with others. However, 61.0% of those exposed did not know or could not remember the purpose of the campaign. Campaign exposure was not associated with higher breastfeeding knowledge (APR [95% confidence interval] = 0.96 [0.73, 1.26]). Breastfeed4Ghana was highly feasible. However, campaign understanding yielded mixed findings and may explain the limited impact on breastfeeding knowledge
Research Article
Keywords: breastfeeding; campaign; feasibility; Ghana; promotion; social media